The IRB as Gatekeeper: Effects on Research with Children and Youth - Harger, Brent; Quintela, Melissa (Researching Children and Youth: Methodological Issues, Strategies, and Innovations, 2017)
Abstract Gatekeepers play an important role in research conducted with children and youth. Although qualitative researchers frequently discuss institutional and individual gatekeepers, such as schools and parents, little attention has been paid to the role that Institutional Review Boards (IRBs) play in determining who is allowed to research particular populations and the ramifications of these decisions for findings involving children and youth. In order to examine this role, we compare negotiations of two researchers working on separate projects with similar populations with the IRB of a large Midwestern university. In both cases, it is likely that board members used their own personal experience and expertise in making assumptions about the race, social class, and gender of the researchers and their participants. The fact that these experiences are supported by findings across a wide range of IRBs highlights the extent to which qualitative research with children is changed (or even prevented) by those with little knowledge of typical qualitative methodologies and the cultural contexts in which research takes place. While those such as principals, teachers, and parents who are traditionally recognized as gatekeepers control access to specific locations, their denial of access only requires researchers to seek other research sites. IRBs, in contrast, control whether researchers are able to conduct research at any site. Although they wield considerably more control over research studies than typical gatekeepers, the fact that they are housed in the institutions at which academic researchers work also means that we can play a role in their improvement.